Invalid usage of Pyrrhulopsis Reichenbach as the generic name for the Fijian shining parrots, Prosopeia Bonaparte, and its consequences - Schodde, Richard; Bock, Walter J.; Watling, Dick; Pacheco, J. Fernando (Zootaxa, 2014)
Recently in this journal, Gregory & Dickinson (2012) replaced Prosopeia Bonaparte,1854, the widely used and long-accustomed generic name for the Fijian shining parrots, with Pyrrhulopsis Reichenbach, 1850. This action was then followed in the influential Howard & Moore global checklist of birds (Dickinson & Remsen 2013: 377) and the websites Avibase (2013) and TiF Checklist (2013). Gregory and Dickinson’s decision rested on information in Kashin (1978), which showed that G.R. Gray (1855) was the first to assign a type species to Pyrrhulopsis Reichenbach. Gray designated “Coracopsis? personata G.R. Gray,1848”, one of the shining parrots, by subsequent monotypy. Until then, Prosopeia had been used for the shining parrots for most of the 20th century into the 21st, following Peters (1937: 250, footnote). Gregory & Dickinson’s (2012) action nevertheless contravenes the purpose of Article 23.2 of the International Code of Zoological Nomenclature, hereafter “the Code”, which stresses that the Principle of Priority is not to be used to upset long-accepted names in their accustomed meaning. Because of this, we had been preparing an application to the International Commission on Zoological Nomenclature to conserve Prosopeia—until we discovered an evident error in Gregory & Dickinson’s argument. The apparent error, which makes application to conserve Prosopeia unnecessary, is explained here to affirm Prosopeia as the valid generic name for the shining parrots.